2017
DOI: 10.2196/jmir.8421
|View full text |Cite
|
Sign up to set email alerts
|

Raising Awareness About Cervical Cancer Using Twitter: Content Analysis of the 2015 #SmearForSmear Campaign

Abstract: BackgroundCervical cancer is the second most common cancer among women under 45 years of age. To deal with the decrease of smear test coverage in the United Kingdom, a Twitter campaign called #SmearForSmear has been launched in 2015 for the European Cervical Cancer Prevention Week. Its aim was to encourage women to take a selfie showing their lipstick going over the edge and post it on Twitter with a raising awareness message promoting cervical cancer screening. The estimated audience was 500 million people. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…They agreed that sexually active or married people should have routine examinations routinely too for prevention and early detection. In a previous study, social media has been found to be an effective platform for increasing knowledge and awareness of cancer 12 .…”
Section: Discussionmentioning
confidence: 99%
“…They agreed that sexually active or married people should have routine examinations routinely too for prevention and early detection. In a previous study, social media has been found to be an effective platform for increasing knowledge and awareness of cancer 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Twitter data have been used in studies on the mental health and suicide prevention field to understand how users discuss mental health issues and why they use social media to do so, to monitor attitudes toward depression and schizophrenia, to gauge how Twitter is used in the provision of feedback and support by mental health services, and to track suicide risk factors [ 29 - 33 ]. In the general health arena, Twitter data have also been used to monitor the impact of campaigns and related interventions (eg, in cervical cancer screening and smoking cessation) [ 34 - 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Social media has been used for medical concerns [18], focusing on recruitment [27], behavior change [16], raising awareness [23] and peer support [36]. Instagram was explored to incentivize physical activity and nutrition habits [11].…”
Section: Related Workmentioning
confidence: 99%